Roses Strewn Upon the Path: Rehearsing Familial Devotion in Late Eighteenth-Century German Songs for Parents and Children - Mueller, Adeline (Frontiers in Communication, 2021)
Intra- and inter-generational family singing is found throughout the world’s cultures. Children’s songs across many traditions are often performed with adult family members, whether simultaneously (in unison or harmony) or sequentially (as in call-and-response). In one corpus of printed children’s songs, however, such musical partnering between young and old was scripted, arguably for the first time. Children’s periodicals and readers in late eighteenth-century Germany offered a variety of poems, theatricals, riddles, songs, stories, and non-fiction content, all promoting norms around filial obedience, virtue, and productivity. Readers were encouraged to share and read aloud with members of their extended families. But the “disciplining” going on in this literature was as much emotional as it was moral. Melodramatic plots to dialogues, plays, and Singspiels allowed for tenderness and affection to be role-played in the family drawing room. And the poems and songs included in and spun off from these periodicals constituted, for the first time, a shared repertoire meant to be sung and played by young and old together. Duets for brothers and sisters, parents and children—with such prescriptive titles as “Brotherly Harmony” and “Song from a Young Girl to Her Father, On the Presentation of a Little Rosebud”—not only trained children how to be ideal sons, daughters, and siblings. They also habituated mothers and fathers to the new culture of sentimental, devoted parenthood. In exploring songs for family members to sing together in German juvenile print culture from 1700 to 1800, I uncover the reciprocal learning implied in text, music, and the act of performance itself, as adults and children alike rehearsed the devoted bourgeois nuclear family.